Rates and Predictors of Relapse in First-Episode Psychosis: An Australian Cohort Study. Issue 1 (11th April 2020) - Brown, Ellie; Bedi, Gillinder; McGorry, Pat; O'Donoghue, Brian
Abstract: Background: Clinical and functional recovery is usually achieved after treatment for a first episode of psychosis (FEP). Unfortunately, subsequent relapse remains common, occurring within a year for approximately 30% of individuals and up to 80% over 5 years. Factors that make relapse more likely in any given individual remain poorly understood. Methods: This article presents a naturalistic cohort study of young people (15–24 years old) accessing an early intervention in psychosis service in Melbourne, Australia between January 1, 2011 and December 31, 2016. Demographic and clinical predictors of relapse were collected and analyzed using Cox regression analysis. Results: A total of 1220 young people presented with an FEP during the study period; 37.7% ( N = 460) experienced at least 1 relapse during their episode of care. Over half of all relapses resulted in an admission to hospital. Non-adherence to medication, substance use, and psychosocial stressors were commonly noted as clinical precipitants of relapse. Significant predictors of relapse (vs no relapse) were a diagnosis of schizophrenia spectrum disorder (adjusted hazard ratio [aHR] = 1.62) or affective psychotic disorder (aHR = 1.37), lifetime amphetamine use (aHR = 1.48), and any substance use during treatment (aHR = 1.63). Conclusion: These findings suggest that relapse occurs frequently for young people who have experienced FEP. This is one of the first studies to report that amphetamine use (predominantly illicit methamphetamine) increases the risk of relapse. Clinical services, especially in Australasia, need to consider how best to manage this comorbidity in young people with FEP.